A diamond gammavoltaic cell utilizing surface conductivity and its response to different photon interaction mechanisms. (September 2021) - Mackenzie, G.R.; Kaluvan, S.; Martin, P.G.; Hutson, C.; Connolley, T.; Cattelan, M.; Dominguez-Andrade, H.; Martin, T.L.; Fox, N.A.; Scott, T.B.
Abstract: This paper presents a diamond gammavoltaic cell—a solid-state device that converts gamma radiation into electricity—with a novel design and promising capabilities. Gammavoltaics pose a unique challenge among radiovoltaics due to the highly penetrating nature of gamma rays. To adapt existing radiovoltaic and dosimeter designs by increasing their thickness risks throttling the flowing current due to an attendant increase in series resistance. The presented design partially decouples this relationship by creating a low-coverage hydrogen-terminated collection volume around the device, exploiting the transfer doping effect. This paper proves that hydrogen termination is necessary for the gammavoltaism exhibited. Data are then presented from current-voltage curves taken using synchrotron radiation over the range 50-150 keV. A drop in the series resistance over the range is discovered and linked to the transition from the photoelectric effect to Compton scattering. The cell produces an open-circuit voltage V OC = 0.8 V. Its short-circuit current I SC and maximum power P max are found to also depend on photon energy, reaching maxima at ∼150 keV, where I SC > 10 μA and P max > 3 μW, normalized in flux to 2 × 10 11 γ.s −1 . Groundwork is hence laid for developing this type of cell for micropower applications. Graphical abstract: Image 1 Highlights: A diamond gammavoltaic was fabricated based on a partial hydrogen-termination. Testing without surface hydrogen showed it was key for the device to function. A drop in resistance corresponding to the Compton transition was observed. Tests using synchrotron radiation generated power in the microwatt range.